Optical Imaging of Integrin α(v) β(3) Expression with Near-Infrared Fluorescent RGD Dimer with Tetra(ethylene glycol) Linkers - Liu, Zhaofei (2010)
Integrin α(v) β(3) plays great roles in tumor angiogenesis, invasion, and metastasis. We report here the noninvasive visualization of tumor integrin α(v) β(3) expression by using near-infrared fluorescence (NIRF) imaging of an IRDye800-labeled new cyclic RGD (arginine-glycine-aspartic acid) dimer with tetra(ethylene glycol) (PEG(4)) linkers (ie, E[PEG(4)-c(RGDfK)](2), PEG(4) = 15-amino-4,7,10,13-tetraoxapentadecanoic acid) in a U87MG tumor model. Fluorescent dye–labeled E[PEG(4)-c(RGDfK)](2) were subjected to in vitro cell staining, in vivo NIRF imaging, ex vivo NIRF imaging, and histologic studies. The in vitro and in vivo characterization of dye-labeled E[PEG(4)-c(RGDfK)](2) were compared with dye-labeled RGD dimer without PEG(4) linkers (namely, E[c(RGDfK)](2)). Both Cy5.5-E[PEG(4) -c(RGDfK)](2) and Cy5.5-E[c(RGDfK)](2) exhibited integrin α(v) β(3) binding specificity in a cell-staining experiment. In vivo NIRF imaging showed higher tumor accumulation and tumor to background contrast of IRDye800-E[PEG(4)-c(RGDfK)](2) over IRDye800-E[c(RGDfK)](2). The tumor integrin α(v) β(3) specificity of IRDye800-E[PEG(4)-c(RGDfK)](2) was confirmed by successful inhibition of tumor uptake in the presence of an excess dose of c(RGDfK). Histologic examination revealed both tumor vasculature and tumor cell integrin α(v) β(3) binding of IRDye800-E[PEG(4)-c(RGDfK)](2) in vivo. In summary, NIRF imaging with IRDye800-E[PEG(4)-c(RGDfK)](2) offers an easy, fast, and low-cost way to detect and semiquantify tumor integrin α(v) β(3) expression in living subjects.